Reduction of interior temperature of massive concrete using an enhanced heat transfer pipe array with spiral fins. Issue 9 (July 2021) - Zhou, Lemu; Zhou, Fangyuan; Peng, Zheng; Ge, Hanbin; Shan, Feng
The interior temperature of the massive concrete should be controlled to avoid cracks caused by the trapped hydration heat. In this paper, an enhanced heat transfer pipe array with spiral fins (PSF) is proposed to reduce the interior temperature of concrete blocks. Numerical simulations of massive concrete blocks embedded with traditional cooling water pipe (TCWP) and newly proposed PSF were conducted to investigate the interior temperature distribution of massive concrete. Meanwhile, validity of the finite element model was verified by both theoretical results and available experimental data. Based on the calculated temperature distribution of the points located in the interior area of the massive concrete, it is shown that when the TCWP was replaced by the PSF, the interior temperature can be significantly reduced. Therefore, compared to the TCWP, the proposed PSF has excellent heat transfer performance for cooling the interior temperature of massive concrete.